Incidence of tennis elbow and association of hand grip strength among college students - B., Riyas Basheer K.; Rai, Subhashchandra; A. M., Irshana Balkies; N. P., Jasim Junaid (International Journal of Research in Medical Sciences, 2020)
Background: Lateral epicondylitis is an overuse injury involving the origin of common extensor tendon at elbow joint. Among the college students there is more complaint on wrist and elbow. Objective was to find out the incidence of tennis elbow & grip strength among the students during the entire academic year. Methods: Three hundred and seventy subjects fulfilled the inclusion criteria with age respondents between seventeen to twenty four years. This study is done in those students who have local tenderness on palpation over the lateral epicondyle (grade 2). NPRS was used for measuring the pain intensity. Mill’s test and Cozen’s test was performed to confirm the tennis elbow. The subject is asked to squeeze the dynamometer three times with left and right hand respectively. There was one minute resting period between each squeeze were taken into account. Results: The incidence of confirmed tennis elbow was 4.05% & 2.70% in right and left respectively. Among those participants Mill’s test was positive in 16.2% on right and left side and Cozen’s test was positive in 8.1% on right side and 5.4% on left side. The mean rank of left and right grip strength for the students who are confirmed as tennis elbow were 52.75 Kg and 50.67 Kg and for not-confirmed were 36.56 Kg and 36.41 Kg respectively. Conclusions: The study concluded that 6.7% incidence rate of tennis elbow was observed in college students during the entire academic year. And also concluded there is no much significance correlation between grip strength and tennis elbow incidence rate.